2005
DOI: 10.1007/s11055-005-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic monoamines in cold stress on the background of changes in the activity of the nitric oxide system

Abstract: The effects of the NO donor sodium nitroprusside and the NO synthase blocker L-omega-N-nitroarginine (LNA) on body temperature, hypothalamic monoamines, and plasma corticosterone in conditions of cooling were studied in Male Wistar rats. Reductions in body temperature on cooling, both after administration of sodium nitroprusside and LNA, were no different from those seen without treatment. The basal corticosterone level after treatment with sodium nitroprusside increased from 5.3 +/- 2.2 to 29.1 +/- 1.8 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The acute cold stress applied in our experiments did not reduce the hypothalamic catecholamine stores of either control or long-term isolated rats. This agrees with the results of Gilinskii et al (21) who found that cold stress did not affect hypothalamic DA content. However, cold stress reduces the DA stores in the hippocampus of control and long-term isolated rats.…”
Section: Discussionsupporting
confidence: 93%
“…The acute cold stress applied in our experiments did not reduce the hypothalamic catecholamine stores of either control or long-term isolated rats. This agrees with the results of Gilinskii et al (21) who found that cold stress did not affect hypothalamic DA content. However, cold stress reduces the DA stores in the hippocampus of control and long-term isolated rats.…”
Section: Discussionsupporting
confidence: 93%
“…The peptides of the Tyr‐MIF‐1 family are termed AOP indicating that the morphine‐induced changes in neuronal responses involve various non‐opioid neurotransmitter networks that participate in a homeostatic system, which acts to dampen the effects of opioids. Some morphological studies provide evidence for the existence of a signalling pathway between an opioidergic and the nitric oxide‐ergic systems in the hypothalamus of the rat brain (Gilinskii et al. , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data that NO plays an important role in regulating the response of the HPA axis to various stressors. Some morphological studies have provided evidence for the existence of a signaling pathway between an opioid-and the nitric oxideergic systems in the hypothalamus of rat brain 44,45,46 . On the other hand, KTP is rapidly metabolized to L-Arg, which ia possible substrate for inducible and neuronal nitric oxide synthase NOS 47 .…”
Section: Discussionmentioning
confidence: 99%